(untitled) - Fielding, Helen (New York, 2000)
A new year begins -- and Bridget Jones, the unflinchingly self-disciplined, and definitely practically nonsmoking heroine, is about to discover what happens when you have the man of your dreams actually in your flat and he hasn't been to the supermarket -- not just tonight, but ever.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy